Shifting relations with the more-than-human: six threshold concepts for transformative sustainability learning. Issue 1 (2nd January 2017) - Barrett, M.J.; Harmin, Matthew; Maracle, Bryan; Patterson, Molly; Thomson, Christina; Flowers, Michelle; Bors, Kirk
Abstract : Using the iterative process of action research, we identify six portals of understanding, called threshold concepts, which can be used as curricular guideposts to disrupt the socially constituted separation, and hierarchy, between humans and the more-than-human. The threshold concepts identified in this study provide focal points for a curriculum in transformative sustainability learning which (1) acknowledges non-human agency; and (2) recognizes that the capacity to work with multiple ways of knowing is required to effectively engage in the process of sustainability knowledge creation. These concepts are: there are different ways of knowing; we can communicate with non-human nature and non-human nature can communicate with us; knowing is relational; transrational intuition and embodied knowing are valuable and valid ways of knowing; worldview is the lens through which we view reality; and the power of dominant beliefs (represented in discourse) supports and/or undermines particular ways of knowing and being as in/valid.